Peritoneal dialysis in acute kidney injury - Response to Dr. Davenport - Gabriel, Daniela Ponce [UNESP] (2008)
Univ Estadual Paulista, Hosp Clin, Dept Internal Med, Fac Med Botucatu, São Paulo, Brazil